Analisis Spasial Perubahan Penggunaan Lahan Serta Faktor-Faktor yang Mempengaruhinya (Studi Kasus Kota Makassar 2011-2019): Spatial Analysis of Land Use Changes and The Affecting Factors (Case Study of Makassar City 2011-2019) - Ahmad Firman Ashari (Universitas Hasanuddin, 2021)
Makassar City as the core city in the Mamminasata National Strategic Area (KSN) has continued to experience population growth since its establishment in 2011. This increase has triggered an increase in demand for land for settlements and other built-up land. Due to the limited availability of land in the city center, there is a phenomenon of land use change in suburban areas. The purpose of this study is to analyze land use changes in Makassar city in the period 2011-2019 and analyze the factors driving changes in land use. The method used is visual interpretation of satellite imagery to obtain land use classes, overlay method to determine land use change and logistic regression method to determine the driving factors of land use change. The results of this study indicate that only three types of land use have increased in area, namely settlements as well as the largest with 29% built-up land by 16% and open land by 5%. While the land uses that experienced a decrease in area from the largest to the smallest respectively were rice fields 18%, ponds 13%, mixed gardens 11%, water bodies 4%, bushes 3%, fields 1%, forests 0.4% and garden 0.1%.